PERBEDAAN KEBOCORAN MIKRO RESIN KOMPOSIT BULKFILL VIBRASISONIC DAN RESIN KOMPOSIT NANOHIBRID PADA KAVITAS KELAS I - , muhammad syafri ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Sonicvibration bulkfill and nanohybrid resin composites are resin composites with nano-fillers. The small particles and the big fillerscapacities enable both resin composites having a very small shrinkage value about 1,6%, therefore, they can minimize the microleakage. The aim of this study was to know the microleakage differences of sonicvibration bulkfill and nanohybrid resin composites in class I cavities. This study used 14 molar teeth. The teeth were divided in two groups, I and II based on the restoration techniques. In Group I, a nanohybrid resin composite with an incrementaltechique was applied and in group II, a sonic vibration bulkfill resin composite using the bulkfilltechnique was applied. Microleakage tests were conducted by soaking the specimens in the solution of methylen blue 2% . The observation of microleakage was done by using a stereo microscope at 100x magnification. The microleakage of the specimens was stated by methylen blue penetration between the restorations and the cavity walls. Data obtained were the ratio data and analyzed by using ttest. The results showed that there were significant differences between the groups (p = 0,046, p<0,05). It was concluded that the microleakage of a nanohybrid resin composite was smaller than a sonic vibration bulkfill resin composite.